(untitled) (La U Investiga, 2020)
The Burnout Syndrome is a type of work stress, considered by the World Health Organization as an occupational disease that leads to the deterioration of physical and mental health in people; since it is believed that it results from the failure of the individual to adapt to work situations that generate high and prolonged stress, continually presenting itself to health professionals. The objective of the present investigation was to characterize the load handled by the health workers of the Hospital Clínica Metropolitana in the city of Ibarra. A descriptive, cross-sectional study was carried out. 40 health workers from the Hospital Clínica Metropolitana were surveyed. Curb the prevalence of the dimensions, it was shown that Personal Realization was 65% for high, Depersonalization 52.5% for low and Emotional Exhaustion 70% for low. A prevalence of 37.5% is considered for mild to moderate Burnout Syndrome in the studied group, which makes it necessary to seek to deepen the study of this syndrome in small health institutions, with the inclusion of cross-cultural factors and particular characteristics, and that allows the comparison of data obtained from institutions of greater size and complexity. It is concluded that the prevalence of Burnout Syndrome is low and the level of personal fulfillment was high in all the workers of the Hospital Clínica Metropolitana.